Plan de marketing turístico para el jardín botánico Reinaldo Espinosa Aguilar de la Universidad Nacional de Loja - Quezada Castillo, Ruth Elizabeth (2016)
In the tourist sector, the importance of the implementation of the Tourist Marketing plan takes root in that this one can turn into the economic growth driver of the zone, generating in addition, a growth in the number of visitors who enter to the different destinations, in turn it is promoted and generates a social and economic impact in the population, creates more sources of employment, which improve the quality of life in the zone where the tourism, major contribution develops to the Internal Brute Product (GDP), because the tourism helps to improve the economy of the different destinations. Also it is important for the additional benefit for the environment and the culture, which transforms in an attraction for the visitor. The tourist sector in the city and Loja province can use as support for the growth of the economy of the zone and to the expansion of the small and medium companies, which will help at the same time to improve the standard of living of the population. The spectacular tourist places that Loja has are of extreme importance for the inhabitants of the city and province and they have been for decades the magnet to attract tourists from all over, in them you will find history, culture, fun and much more. Botanical Garden Reinaldo Espinosa is considered it a natural laboratory, was founded in 1949 by the distinguished botanist Reinaldo Espinosa, in order to promote research and environmental conservation. For such a reason the qualified topic becomes present: " TOURIST MARKETING PLAN FOR THE BOTANICAL GARDEN REINALDO ESPINOSA AGUILAR OF LOJA NATIONAL UNIVERSITY ", due to the fact that this attraction lacks a promotion and suitable and identical diffusion to his importance and path due to the fact that it is a question of the most ancient botanical garden of the Ecuador. To develop the process of investigation there were established aims directed to the fulfillment of the present work; since General Aim is: To elaborate a Tourist Marketing plan for the Botanical Garden Reinaldo Espinosa Aguilar, of Loja National University, for which there were established two specific aims, the first one is: Reinaldo Espinosa Aguilar Realizes a Diagnosis of the current situation of the Botanical Garden; and the second one consists in: Reinaldo Espinosa Aguilar Proposes a tourist marketing plan for the Botanical Garden. The methodology applied in this study was realized on the basis of the aims established of the following way: to realize the Diagnosis of the current situation of the Botanical Garden Reinaldo Espinosa Aguilar, one used the methods analytical, quantitatively, descriptively together with the technologies of the observation, interview and survey. To carry out the Offer of the tourist marketing plan for the Botanical Garden Reinaldo Espinosa Aguilar, the analytical method was used; this one served for the analysis and processing of information obtained previously, hereby to obtain a better addressing to the moment to elaborate the raised offer. The results obtained across the methods and applied technologies of investigation and before mentioned they were important to obtain relevant information, and to realize a deep analysis and on the basis of this to raise the strategic aims of the Tourist Marketing plan. For the external diagnosis or macro-environment, the raising of information was realized, by means of five factors since they are: demographic, economic, political - legal, sociocultural and technological Factor, of equal form I consider the results of the surveys applied to the tourists and visitors of the Garden. For the Internal diagnosis or micro-environment information compiled by means of investigation was in use and across the interview realized to the Director in charge of the Botanical Garden. With the analysis of the results of the external and internal diagnosis it was possible to define the Marketing plan. As for the conclusions the principal zeal is considered to be opportune Reinaldo Espinosa Aguilar Elaborates a Tourist Marketing plan for the Botanical Garden, since it is a site of interest and great importance to level Place - native, and on having identified some weaknesses inside the place is to promote the tourism and the frequent visits to the Botanical Garden across the strategies before mentioned that definitively meet here reflected in this work of investigation, which represents in logical, clear and concise form the obtained results, on the basis of a good study that precedes the project in yes. The recommendations were elaborated resting on the conclusions themselves that try to be the reflection of future actions directed to involving in a direct way to Loja National University, tourist sector, and citizenship in general with the zeal to promote a joint development.